G528(P) Improving paediatric autism assessment services in a district general hospital: a completed audit. (May 2019) - Ritzmann, TA; Herath, D; Lee, AM; Chhaochharia, A; Johnson, F
Abstract : Introduction: One percent of the population have an autistic spectrum disorder (ASD). The National Institute for Healthcare and Excellence (NICE) makes recommendations regarding diagnostic assessments for autism to allow appropriate interventions, advice and support to be offered. We present a completed audit to share our experience of redesigning an ASD assessment pathway to better serve the local community. Methods: Initial audit of 51 cases in 2016 identified deficiencies in our autism assessment strategy triggering re-design. The new pathway involves four stages: (1) information gathering; (2) Paediatrician and Speech and Language Therapist (SLT) assessment; (3) Autism Diagnostic Observation Schedule (ADOS) assessment if diagnosis unclear at stage two; (4) Care planning meeting (written report, signposting to appropriate services, and provision of an information pack). We integrated the use of a social communication report (SCR) prepared by SLT into stage two to reduce ADOS assessments. In 2018, following pathway initiation, we re-audited 48 cases against local and NICE standards (table 1 ), aiming for 100% compliance. Results: Time for first contact with the autism assessment team fell from three to two months. SCR, care planning meetings and information packs were unavailable in 2016. Some patients waited long periods of time for their care planning meeting (42% seen within six-weeks). Most patients who were diagnosed with an ASD received an information pack (78%) and all had written reports. Large improvement was seen in multidisciplinary diagnoses (0% in 2016, 100% in 2018). Discussion: Overall, we saw an improvement in the service provided to patients through more robust multidisciplinary diagnoses. A key challenge was the volume of ADOS assessments stretching SLT resources. We are making changes to address this including joint meetings between paediatrics and SLT to discuss borderline cases. Discussion with CCGs is ongoing to ensure further improvement to our service.